Charge transfer events in semiconducting single-wall carbon nanotubes - Oelsner, Christian; Antonia Herrero, M.; Ehli, Christian; Prato, Maurizio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2011)
Electron-donating ferrocene units have been attached to SWNTs, with different degrees of functionalization. By means of a complementary series of novel spectroscopic techniques (i.e., steady-state and time-resolved), we have documented that mutual interactions between semiconducting SWNT and the covalently attached electron donor (i.e., ferrocene) lead, in the event of photoexcitation, to the formation of radical ion pairs. In the accordingly formed radical ion pairs, oxidation of ferrocene and reduction of SWNT were confirmed by spectroelectrochemistry. It is, however, shown that only a few semiconducting SWNTs [i.e., (9,4), (8,6), (8,7), and (9,7)] are susceptible to photoinduced electron transfer processes. These results are of relevant importance for the development of SWNT-based photovoltaics. © 2011 American Chemical Society.

Cruciforms' polarized emission confirms disjoint molecular orbitals and excited states - Gard, Matthew N.; Zucchero, Anthony J.; Kuzmanich, Gregory; Oelsner, Christian; Guldi, Dirk Michael; Dreuw, Andreas; Bunz, Uwe H. F.; Garcia-Garibay, Miguel A. (Organic Letters, 2012)
Steady-state and time-resolved polarized spectroscopy studies reveal that electronic excitation to the third excited state of 1,4-distyryl-2,5- bis(arylethynyl)benzene cruciforms results in fluorescence emission that is shifted an angle of ca. 60°. This result is consistent with quantum chemical calculations of the lowest electronic excited states and their transition dipole moments. The shift originates from the disjointed nature of the occupied molecular orbitals being localized on the different branches of the cruciforms. © 2012 American Chemical Society.

Efficient utilization of higher-lying excited states to trigger charge-transfer events - Bouit, Pierre-Antoine; Spänig, Fabian; Kuzmanich, Gregory; Krokos, Evangelos; Oelsner, Christian; Garcia-Garibay, Miguel A.; Delgado, Juan Luis; Martin, Nazario; Guldi, Dirk Michael (Chemistry - A European Journal, 2010)
Several new fullerene-heptamethine conjugates, which absorb as far as into the infrared spectrum as 800 nm, have been synthesized and fully characterized by physicochemical means. In terms of optical and electrochemical characteristics, appreciable electronic coupling between both electroactive species is deduced. The latter also reflect the excited-state features. To this end, time-resolved, transient absorption measurements revealed that photoexcitation is followed by a sequence of charge-transfer events which evolve from higher singlet excited states (i.e., S-fast charge transfer) and the lowest singlet excited state of the heptamethine cyanine (i.e., S - slow charge transfer), as the electron donor, to either a covalently linked C or C as the electron acceptor. Finally, charge transfer from photoexcited C/ C completes the charge-transfer sequence. The slow internal conversion within the light-harvesting heptamethine cyanine and the strong electronic coupling between the individual constituents are particularly beneficial to this process. © 2010 Wiley-VCH Verlag GmbH&Co. KGaA, Weinheim.

Excited state properties of anodic TiO2 nanotubes - Kahnt, Axel; Oelsner, Christian; Werner, Fabian; Guldi, Dirk Michael; Albu, Sergiu; Kirchgeorg, Robin; Lee, Kiyoung; Schmuki, Patrik (Applied Physics Letters, 2013)
Charge carriers, that is, holes as well as trapped and "free" electrons were investigated by means of time resolved spectroscopy in anodic TiO nanotubes that were heat treated at different temperatures. The lifetimes of the charge carrier were compared with those generated in reference layers of Solaronix Ti-Nanoxide D and Degussa P25 nanoparticles. Remarkably long lived "free" electrons were only noted in the TiO nanotubes. These findings have significance in view of any photoelectrochemical applications of TiO nanotubes. © 2013 2013 Author(s).

Immobilizing water-soluble dendritic electron donors and electron acceptors - Phthalocyanines and perylenediimides - Onto single wall carbon nanotubes - Hahn, Uwe; Engmann, Sarah; Oelsner, Christian; Ehli, Christian; Guldi, Dirk Michael; Torres, Tomas (Journal of the American Chemical Society, 2010)
The complementary use of spectroscopy and microscopy sheds light onto mutual interactions between semiconducting single wall carbon nanotubes (SWNT) and either a strong dendritic electron acceptor - perylenediimide - or a strong dendritic electron donor - phthalocyanine. Importantly, the stability of the perylenediimide/SWNT electron donor-acceptor hybrids decreases with increasing dendrimer generation. Two effects are thought to be responsible for this trend. With increasing dendrimer generation we enhance (i) the hydrophilicity and (ii) the bulkiness of the resulting perylenediimides. Both effects are synergetic and, in turn, lower the immobilization strength onto SWNT. Owing to the larger size of the phthalocyanines, phthalocyanine/SWNT electron donor-acceptor hybrids, on the other hand, did not reveal such a marked dependence on the dendrimer generation. Several spectroscopies confirmed that distinct ground- and excited-state interactions prevail and that kinetically and spectroscopically well-characterized radical ion pair states are formed within a few picoseconds. © 2010 American Chemical Society.

Interfacing strong electron acceptors with single wall carbon nanotubes - Oelsner, Christian; Schmidt, Cordula; Hauke, Frank; Prato, Maurizio; Hirsch, Andreas; Guldi, Dirk Michael; Hauke, Frank (Journal of the American Chemical Society, 2011)
The complementary use of steady-state and time-resolved spectroscopy in combination with electrochemistry and microscopy are indicative of mutual interactions between semiconducting SWNTs and a water-soluble strong electron acceptor, i.e., perylenediimide. Significant is the stability and the strong electronic coupling of the perylenediimide/SWNT electron donor-acceptor hybrids. Several spectroscopic and spectroelectrochemical techniques, i.e., Raman, absorption, and fluorescence, confirmed that distinct ground- and excited-state interactions occur and that kinetically and spectroscopically well characterized radical ion pair states form within a few picoseconds. © 2011 American Chemical Society.

Manipulating single-wall carbon nanotubes by chemical doping and charge transfer with perylene dyes - Ehli, Christian; Oelsner, Christian; Guldi, Dirk Michael; Mateo-Alonso, Aurelio; Prato, Maurizio; Schmidt, Cordula; Backes, Claudia; Hauke, Frank; Hirsch, Andreas; Hauke, Frank (Nature Chemistry, 2009)
Single-wall carbon nanotubes (SWNTs) are emerging as materials with much potential in several disciplines, in particular in electronics and photovoltaics. The combination of SWNTs with electron donors or acceptors generates active materials, which can produce electrical energy when irradiated. However, SWNTs are very elusive species when characterization of their metastable states is required. This problem mainly arises because of the polydispersive nature of SWNT samples and the inevitable presence of SWNTs in bundles of different sizes. Here, we report the complete and thorough characterization of an SWNT radical ion-pair state induced by complexation with a perylene dye, which combines excellent electron-accepting and-conducting features with a five-fused ring-system. At the same time, the perylene dye enables the dispersion of SWNTs by means of- interactions, which gives individual SWNTs in solution. This work clears a path towards electronic and optoelectronic devices in which regulated electrical transport properties are important. © 2009 Macmillan Publishers Limited. All rights reserved.

Metallic-like stoichiometric copper sulfide nanocrystals: Phase- and shape-selective synthesis, near-infrared surface plasmon resonance properties, and their modeling - Xie, Yi; Carbone, Luigi; Nobile, Concetta; Grillo, Vincenzo; D'Agostino, Stefania; Della Sala, Fabio; Giannini, Cinzia; Altamura, Davide; Oelsner, Christian; Kryschi, Carola; Cozzoli, P. Davide (Acs Nano, 2013)
In the realm of semiconductor nanomaterials, a crystal lattice heavily doped with cation/anion vacancies or ionized atomic impurities is considered to be a general prerequisite to accommodating excess free carriers that can support localized surface plasmon resonance (LSPR). Here, we demonstrate a surfactant-assisted nonaqueous route to anisotropic copper sulfide nanocrystals, selectively trapped in the covellite phase, which can exhibit intense, size-tunable LSPR at near-infrared wavelengths despite their stoichiometric, undoped structure. Experimental extinction spectra are satisfactorily reproduced by theoretical calculations performed by the discrete dipole approximation method within the framework of the Drude-Sommerfeld model. The LSPR response of the nanocrystals and its geometry dependence are interpreted as arising from the inherent metallic-like character of covellite, allowed by a significant density of lattice-constitutional valence-band free holes. As a consequence of the unique electronic properties of the nanocrystals and of their monodispersity, coherent excitation of symmetric radial breathing modes is observed for the first time in transient absorption experiments at LSPR wavelengths. © 2013 American Chemical Society.

Synthesis and physico-chemical properties of porphycenes - Brenner, Wolfgang; Malig, Jenny; Oelsner, Christian; Guldi, Dirk Michael; Jux, Norbert (Journal of Porphyrins and Phthalocyanines, 2012)
A new and improved synthesis for porphycenes is presented. In particular, treating pyrroles with iodine monochloride results in quantitative yields and easier work up. This key step was employed for the synthesis of different 2,7,12,17-substituted porphycenes (TPrPc, TPPc, TtBPPc). The synthetic part of this project is followed by a global analysis of the physico-chemical properties of three exemplary porphycenes, including absorption, emission, and electrochemistry. In-situ UV-vis/nIR spectroelectrochemistry was used to determine the spectral signatures of the radical anion and cation species. Temperature-dependent fluorescence lifetimes were determined under air as well as under inert atmosphere. © 2012 World Scientific Publishing Company.

Ultrafast excitation energy transfer in vinylpyridine terminated silicon quantum dots - Sommer, Anja; Cimpean, Carla Ramona; Kunz, Michael; Oelsner, Christian; Kupka, Hans J.; Kryschi, Carola (Journal of Physical Chemistry C, 2011)
Water-soluble 2- and 4-vinylpyridine terminated silicon quantum dots (SiQDs) with sizes between 2 and 3 nm were obtained by HF etching of oxidized SiQDs and subsequently passivating with vinylpyridine ligands via thermal hydrosilylation. The functionalized SiQDs emit photoluminescence in the blue-green spectrum with quantum yields around 30%. The photoluminescence is ascribed to radiative recombination of excitons confined to the SiQD core. Indication of efficient electronic interactions between excited ligand states and SiQD conduction band states has been achieved by real-time monitoring excitation relaxation dynamics on the subpicosecond time scale using time-resolved laser spectroscopy techniques. The observed ultrafast excitation relaxation dynamics involving decay and rise dynamics faster than 1 ps were ascribed to electronic excitation energy transfer from an initially photoexcited ligand state to SiQD conduction band states. These results were analyzed by performing a state population analysis on the basis of electron exchange interactions. © 2011 American Chemical Society.